Pengaruh Kepemimpinan terhadap Disiplin Kerja Pegawai Kantor Kementerian Agama Kota Bukittinggi dengan Motivasi Kerja Sebagai Variabel Moderating - Dasep Suryanto (Management Studies and Entrepreneurship Journal (MSEJ), 2019)
The results showed that the influence between leadership and work discipline was significant. The influence between leadership and work motivation was also significant. The influence between work motivation cannot strengthen the leadership relationship to Work Discipline and is not significant. with a T-statistic of 1,2572541846236 (<1,960). The original sample estimate value is negative, amounting to -0.13494828, which shows that the direction of the relationship between Leadership and Work Discipline which is moderated by motivational variables has a negative and insignificant effect, while the influence between leadership and work discipline at the Office of the Ministry of Religion in Bukittinggi has a positive influence. and significant, so does the influence of leadership on motivation has a positive and significant influence and finally the influence of motivation on work discipline at the Office of the Ministry of Religion in Bukittinggi has a positive and significant effect so that all hypotheses submitted can be accepted except the leadership hypothesis in moderation of work motivation variables working discipline at the Bukittinggi City Ministry of Religion's Office is unacceptable. Keywords: Leadership, Motivation and Discipline